2012
DOI: 10.5402/2012/957283
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Obesity, Glucose Intolerance, and Oxidative Stress in High-Fat Diet and Low-Dose Streptozotocin-Induced Diabetic Rats by Combination Consisting of “Curcumin with Piperine and Quercetin”

Abstract: Curcumin is an important nutraceutical that has enormous potential for a variety of diseases, but the medicinal properties of curcumin cannot be utilized due to its low in vivo bioavailability. Therefore, in view of the foregoing, there is an extensive need for combinatorial extract “curcumin with piperine and quercetin” which may enhance bioavailability of oral curcumin by inhibiting the enzymes responsible for the metabolism of curcumin. Thus, the present study investigated the effect of combinatorial extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 22 publications
6
24
0
Order By: Relevance
“…Oxidative stress in rats due to high fat diet feeding also increases the glucose intolerance and insulin resistance [42, 43]. Our investigation also revealed that high fat diet increased plasma and tissues level of oxidative stress markers.…”
Section: Discussionsupporting
confidence: 54%
“…Oxidative stress in rats due to high fat diet feeding also increases the glucose intolerance and insulin resistance [42, 43]. Our investigation also revealed that high fat diet increased plasma and tissues level of oxidative stress markers.…”
Section: Discussionsupporting
confidence: 54%
“…Literature review showed curcumin attracted increasing attention for the treatment of a range of conditions because of its numerous health benefits and people consuming curcumin in daily life have better health status [6,7,[36][37][38][39]. Due to side effects of chemical drugs, except in severe cases, chemical drugs consumption is not recommended for treating PMS.…”
Section: Discussionmentioning
confidence: 97%
“…Since GSH is utilized for detoxification of free radicals, increased sensitivity to oxidative stress also occurs when cells are depleted of GSH (Chen et al, 1997;Kaur and Meena, 2012;Sehgal et al, 2012). Curcumin has been found to show promising increase in superoxide dismutase activity with comparable free radical scavenging ability and an improved antioxidant efficacy (Barik et al, 2005;Girish and Pradhan, 2012;Kaur and Meena, 2012;Sehgal et al, 2012). Curcumin thus is a potent dietary antioxidant against ROS and ROS induced cellular damage (Singh and Giri, 2012).…”
Section: Discussionmentioning
confidence: 99%